Proposing a Strategic Framework to Accelerate Circular Economic Practices: Strengthening the Willingness to Participate of the Young Generations as Agents of Change - Maya Maria; Imas Maesaroh; Ginta Ginting (Journal of International Conference Proceedings, 2022)
ABSTRACT Indonesia's involvement in supporting the reduction of greenhouse gas (GHG) emissions (Conference of the Parties-26/COP-26) in overcoming economic, social and environmental problems through low-carbon development, requires the acceleration of the implementation of Circular Economy (CE) practices. Circular Economy (Reduce, Reuse, Recycle, Recovery and Repair) is an alternative to switch from a linear/traditional economy (take-make-dispose). This research is aimed at exploring the extent to which the role of the younger generation (in terms of preferences, mindsets, and expectations) to become agents of change to accelerate the implementation of good practices in the CE.  A survey with a descriptive method involving 253 respondents (the younger generation) found that respondents did not mind being agents of change (with the range of answers agree and strongly agree was above 70%) to participate for the success of the CE practices, especially related to the desire to invite others to implement the CE economic practices (87%), willingness to dedicate time to set a positive example and be a part of a community that cares about the practices of  CE (84%). The findings of this research are then used as the basis for building a comprehensive CE model to examine its 3 dimensions, namely: stakeholder management, community engagement, and knowledge creation. Keywords: Circular Economy, Agent of Change, Stakeholder Management, Community Engagement, Knowledge Creation.